Not All Time Is Money: Women's Burden of Unpaid Work. Issue 2 (December 2020) - Bhuta, Aishwarya; Muralidharan, Mridula
Since the 1990s, India has been witnessing a downward trend in female labour force participation (FLFP). Feminist economists have argued that the invisible labour of unpaid household work is quintessential for the social reproduction of the labour force. Time-use statistics can be useful for estimating the value of unpaid work and lead policy responses towards increasing FLFP. This study analyses the report on Time Use in India-2019 to draw insights from data on women's disproportionate burden of unpaid domestic and caregiving services. It is argued that this has implications for their participation in the labour market. The patriarchal structure of the family pushes the onus of domestic labour on women. This confines them to home-based, poorly remunerated and informal work, or excludes them from the labour market. Interventions in the form of generating non-agricultural job opportunities in rural areas, establishing infrastructural support mechanisms in workplaces and encouraging female education and employment can not only stimulate FLFP but also help to address the crisis of jobless growth.